Clinical Features of Myasthenia Gravis With Antibodies to MuSK Based on Age at Onset: A Multicenter Retrospective Study in China - Zhou, Yufan; Chen, Jialin; Li, Zunbo; Tan, Song; Yan, Chong; Luo, Sushan; Zhou, Lei; Song, Jie; Huan, Xiao; Wang, Ying; Zhao, Chongbo; Zeng, Wenshuang; et al. (Frontiers in Neurology, 2022)
Introduction Antibodies to MuSK identify a rare subtype of myasthenia gravis (MuSK-MG). In western countries, the onset age of MuSK-MG peaks in the late 30's while it is unknown in Chinese population. Methods In this retrospective multicenter study, we screened 69 MuSK-MG patients from 2042 MG patients in five tertiary referral centers in China from October 2016 to October 2021 and summarized the clinical features and treatment outcomes. Then we subgrouped the patients into early-onset (<50 years old), late-onset (50–64 years old), and very-late-onset (≥65 years old) MG and compared the differences in weakness distribution, disease progression and treatment outcomes among three subgroups. Results The patients with MuSK-MG were female-dominant (55/69) and their mean age at onset was 44.70 ± 15.84 years old, with a broad range of 17–81 years old. At disease onset, 29/69 patients were classified as MGFA Type IIb and the frequency of bulbar and extraocular involvement was 53.6 and 69.6%, respectively. There was no difference in weakness distribution. Compared with early-onset MuSK-MG, very-late-onset patients had a higher proportion of limb muscle involvement (12/15 vs.16/40, p = 0.022) 3 months after onset. Six months after onset, more patients with bulbar (14/15 vs. 26/39, p = 0.044) and respiratory involvement (6/15 vs. 0/13, p = 0.013) were seen in very-late-onset than in late-onset subgroup. The very-late-onset subgroup had the highest frequency of limb weakness (86.7%, p < 0.001). One year after onset, very-late-onset patients demonstrated a higher frequency of respiratory involvement than early-onset patients (4/12 vs. 2/35, p = 0.036). 39/64 patients reached MSE. Among 46 patients who received rituximab, very-late-onset patients started earlier than late-onset patients [6 (5.5–7.5) vs. 18 (12–65) months, p = 0.039], but no difference in the time and rate to achieving MSE was identified. Conclusion MuSK-MG patients usually manifested as acute onset and predominant bulbar and respiratory involvement with female dominance. Very-late-onset patients displayed an early involvement of limb, bulbar and respiratory muscles in the disease course, which might prompt their earlier use of rituximab. The majority MuSK-MG patients can benefit from rituximab treatment regardless of age at onset.